2004
DOI: 10.1140/epjc/s2004-02030-1
|View full text |Cite
|
Sign up to set email alerts
|

Low x particle spectra in the modified leading logarithm approximation

Abstract: We show that the higher moments of the evolution obtained from the Modified Leading Logarithm Approximation may be regarded as spurious higher order terms in perturbation theory, and that neglecting them leads to a good description of the data around and above the peak in ξ = ln(1/x). Furthermore, we use this study of the moments to show that at high energy the Limiting Spectrum with Local Parton-Hadron Duality may also be derived from the Modified Leading Logarithm Approximation without any non-perturbative a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…[12], which was pointed out and remedied in Ref. [9]. Figure 3 in fact shows that the evolution at large ξ follows the data well.…”
Section: B Incorporation Of Soft Gluon Resummationsupporting
confidence: 58%
See 4 more Smart Citations
“…[12], which was pointed out and remedied in Ref. [9]. Figure 3 in fact shows that the evolution at large ξ follows the data well.…”
Section: B Incorporation Of Soft Gluon Resummationsupporting
confidence: 58%
“…In Ref. [9], this inability to describe large ξ (small x p ) data using the naive approach to the MLLA was attributed to the formally beyond-MLLA evolutions of the higher moments (skewness, kurtosis etc.) becoming too large at large √ s, and when these were fixed to be zero it was found that the MLLA could give an excellent description of data up to the highest values of ξ currently measured.…”
Section: Comparisons With Datamentioning
confidence: 99%
See 3 more Smart Citations